2017
DOI: 10.3171/2016.8.jns16992
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression of the cochleovestibular nerve for treatment of tinnitus and vertigo: a systematic review and meta-analysis of individual patient data

Abstract: OBJECTIVE Microvascular decompression (MVD) is regarded as a valid treatment modality in neurovascular conflicts (NVCs) causing, for example, trigeminal neuralgia and hemifacial spasms. An NVC of the cochleovestibular nerve might cause tinnitus and/or vertigo; however, general acceptance of MVD for this indication is lacking. The aim of this study was to investigate the effectiveness, safety, and prognostic factors for success of MVD of the cochleovestibular nerve. METHODS A systematic review and meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In a recent meta-analysis, the success rate for CN8 MVD was 28% for tinnitus and 32% for tinnitus and vertigo, respectively. 19 Interestingly, when those complaints coexisted, MVD was successful in relieving almost twice as many patients (62%) from their symptoms. 19 This finding suggests that when both complaints occur in the same individual, the underlying pathology is more likely to be NVC, thereby making MVD an appropriate procedure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent meta-analysis, the success rate for CN8 MVD was 28% for tinnitus and 32% for tinnitus and vertigo, respectively. 19 Interestingly, when those complaints coexisted, MVD was successful in relieving almost twice as many patients (62%) from their symptoms. 19 This finding suggests that when both complaints occur in the same individual, the underlying pathology is more likely to be NVC, thereby making MVD an appropriate procedure.…”
Section: Discussionmentioning
confidence: 94%
“…19 Interestingly, when those complaints coexisted, MVD was successful in relieving almost twice as many patients (62%) from their symptoms. 19 This finding suggests that when both complaints occur in the same individual, the underlying pathology is more likely to be NVC, thereby making MVD an appropriate procedure. It should be noted that therapeutic success was defined as complete relief from tinnitus and/or vertigo, because partial resolution is not standardized and difficult to compare among studies.…”
Section: Discussionmentioning
confidence: 94%
“…31,56 The most common presentation of epidermoids is headache (67%). 57 The most common cranial nerve deficit at presentation involve the vestibulocochlear nerve but these occur in a fewer percentage of patients compared with VS (50-80%). 32 Trigeminal and facial nerve are involved in 30 to 50%.…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…A recent systematic review included 572 patients from 35 studies. 57 They reported that only 28% of patients with tinnitus had complete symptom of relief with MVD with more than one complication noted in 11% of patients. Interestingly, patients with both tinnitus and vertigo had a higher chance of success than in those with tinnitus alone.…”
Section: Microvascular Decompressionmentioning
confidence: 99%
See 1 more Smart Citation